Internal environmental policy based on green procurement for construction project / Zafikha Aida Bidin ... [et al.] - Bidin, Zafikha Aida; Mohamad Bohari, Asmah Alia; Khalil, Natasha; Mohd Sabri, Noor Syafiqah; Mohd Mustafa, Siti Nurul Ainun (2022)
Industries around the world must move towards green operation to minimise environmental degradation impacts. Construction sector is one of the contributors to environmental degradation, and thus, prompting the government to introduce approaches and initiatives to manage the environmental issues. Government intervention is crucial to steer the industry towards a greener direction. The government's enforcement in terms of policies and guidelines on sustainable construction are the most effective way in persuading the industry. Green procurement is one of the initiatives introduced; however, there is a missing link on how the construction stakeholders can utilise green procurement to support the shift towards a green approach. Thus, this article aims to review the currently available Malaysian government's policies and guidelines, and provide justifications on the adoption of green procurement as one of the environmental policies for construction projects. This paper sets the groundwork for future environmentally friendly construction research in Malaysia, mainly in green procurement practices. The fact that green procurement for the construction industry is still very new in Malaysia, this article will contribute towards the body of knowledge and create awareness on the usefulness of green procurement.